2016
DOI: 10.1177/1077559516630831
|View full text |Cite
|
Sign up to set email alerts
|

Development, CAPTA Part C Referral and Services Among Young Children in the U.S. Child Welfare System

Abstract: Amendments made to the Child Abuse Prevention and Treatment Act in 2003 and the Individuals with Disabilities Education Improvement Act in 2004 opened the door to a promising partnership between child welfare services and early intervention (EI) agencies by requiring a referral to EI services for all children under age 3 involved in a substantiated case of child abuse, neglect, or illegal drug exposure. However, little research has been conducted to assess the implications of these policies. Using data drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Amongst children with a developmental disability, a report of emotional maltreatment and out-of-home placement were two factors that increased the likelihood of a service referral for a formal assessment [ 39 ]. The likelihood of a referral to developmental services was more likely for cases in which the child welfare system had determined a need for services and where children experienced sexual abuse [ 40 ].There is a dearth of research that explores service referrals for infants and young children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst children with a developmental disability, a report of emotional maltreatment and out-of-home placement were two factors that increased the likelihood of a service referral for a formal assessment [ 39 ]. The likelihood of a referral to developmental services was more likely for cases in which the child welfare system had determined a need for services and where children experienced sexual abuse [ 40 ].There is a dearth of research that explores service referrals for infants and young children.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there are differences between the U.S. and Canada in how the knowledge of early childhood development has informed child welfare legislation and policies. In the U.S., amendments were made in 2003 to the Child Abuse and Prevention Act (CAPTA) in recognition of the importance of early intervention for young child welfare-involved children [ 11 , 40 ]. Funded under Part C of the Individuals with Disabilities Education Improvement Act (IDEA), states were required to develop referral procedures to early intervention services for children aged 0 to 3 years who were involved in a substantiated case of child maltreatment [ 11 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research connects child maltreatment and early trauma exposure to mental health and developmental concerns in infants, toddlers, and preschool children (Grasso, Ford, & Briggs-Gowan, 2013; Johnson-Motoyama, Moses, Conrad-Hiebner, & Mariscal, 2016; Harden, Buhler, & Parra, 2016; Milot, St-Laurent, Ethier, & Provost, 2010; Mongillo, Briggs-Gowan, Ford, & Carter, 2009; Scarborough & McCrae, 2010). A 2009 study shows one in four toddlers between the ages of 18 months and 36 months experience potentially traumatic events (PTE; Mongillo et al, 2009).…”
mentioning
confidence: 99%
“…Scarborough and McCrae (2010) found that in the U.S. population, children under 3 years of age experience the highest substantiated rates of PTEs including physical abuse, severe injury, and longer out of home placements. Multiple studies report that over 45% of infants and toddlers experiencing child maltreatment have significant developmental delays before the age of 3 years (Johnson-Motoyama et al, 2016; Rosenberg & Smith, 2008) and display high rates of poor adaptive and social emotional skills when they enter school (Scarborough & McCrae, 2010). Child welfare (CW) and public instruction entities keep independent data systems, placing significant challenges on gathering data.…”
mentioning
confidence: 99%